Pengaruh Uang Muka Dan Termin Pada Target Keuntungan Pihak Penyedia Jasa Proyek Konstruksi - Yanita, Rachmi; Wanuri, Fauzan (KILAT, 2024)
The method of payment for construction project costs is regulated in the construction contract, namely without and with down payments and or terms. Down payment can be given, regulated in presidential, government and LKPP regulations regarding the procurement of goods and services where the aim is to assist service providers or contractors in the preparation stage for construction work. The purpose of this study was to determine the effect of the presence of down payment and terms of a study project contract without down payment on the targeted profit. The research method is carried out by analyzing the cash flow of the project with a variation of 0% down payment, and 10% without and with a term of 15%,25% and 50% of the project value. Cash flow describes the flow of receipts and expenditures of project costs whose balances cannot be negative for the continuity of the project. Data obtained through intensive interviews with contractors includes direct and indirect project costs, project schedules and S-curves, timing of disbursement of invoices, and targeted profits. From the results of the analysis it was found that without a down payment, the amount of profit or final cash balance was 13.05% or below the targeted 15%, while with an advance the profit was 15.71% and 17.56% plus the term after achievement above 25%. Down payments and terms have a positive effect on contractor profits in line with declining loans and interest on loans. Keywords: cash flow, down payment, term, profit